Information and Communication Technology-Based Education and Learning Challenges in The Industrial Age 5.0 - Riyanto Wujarso; Saprudin Saprudin; Revan Andhitiyara (Goodwood Publishing, 2026)
Purpose: To analyze the challenges and adaptation strategies of Information and Communication Technology (ICT)-based education in the Industry 5.0 era, with a focus on the impact of the integration of the Internet of Things (IoT) and Artificial Intelligence (AI) on student character and the readiness of the learning ecosystem. Research methodology: Descriptive qualitative analysis methods were used to evaluate social phenomena, perceptions, and the readiness of educational elements to adapt to digital transformation in depth. Results: The findings indicate a shift in student character due to the dominance of technology, the urgency of character-based curriculum reform, the need to improve teachers' digital competencies, and the crucial importance of equitable ICT infrastructure as a key enabler. Conclusions: Education in the 5.0 era requires a balance between technological advancement and strengthening humanism. The synergy between an adaptive curriculum, competent teachers, and adequate infrastructure is key to producing a generation that is innovative yet strong in character. Limitations: This study is limited to a descriptive qualitative analysis of the geographical context of developing countries, specifically Indonesia. Consequently, the interpretive findings are highly contextual and not intended for broad statistical generalization across different global demographics or advanced educational ecosystems. Contributions: This study provides a strategic foundation for designing an education roadmap that is responsive to Industry 5.0 and enriches the literature on education management by maintaining moral values amid technological disruption.